Enhancement of energy harvesting using acoustical-black-hole-inspired wave traps. (22nd May 2019) - Maugan, Fabien; Chesne, Simon; Monteil, Melodie; Collet, Manuel; Yi, Kaijun
Abstract: The purpose of this paper is to highlight the interest of associating smart functionalities in the same smart-structure. It consists in combining a wave trap device with an energy harvester on a beam. Both functions are performed using piezoelectric transducers. The wave trap device is based on the acoustical black hole concept. It is designed to generate a gradual modification of the equivalent composite Young's modulus along the beam. The aim is to concentrate the mechanical energy at the beam center where the harvesting device is placed. To achieve this, a network of transducers is used. The transducers are shunted on a specific negative capacitance. The harvester device is made of a simple piezoelectric patch associated with a classical extracting circuit. A significant increase in harvested energy is observed using this association for both weak and strong coupling. From the practical viewpoint, the study also highlights the sensitivity of the structural behavior, which strongly depends on the tuning of the trap device.